2020
DOI: 10.1021/acsenergylett.0c01130
|View full text |Cite
|
Sign up to set email alerts
|

Antisolvent Additive Engineering Containing Dual-Function Additive for Triple-Cation p–i–n Perovskite Solar Cells with over 20% PCE

Abstract: In this work, we attempt to improve the quality of the perovskite film using a functional additive in the perovskite antisolvent, which is known as antisolvent additive engineering (AAE). An AAE additive, 2-hydroxyethyl acrylate (HEA), that includes −OH and CO functional groups is introduced into the antisolvent. Its effect on the perovskite film and devices is then systematically studied. Comprehensive analyses including cell performance, carrier transport dynamics, and perovskite surface and morphology meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 58 publications
11
92
0
Order By: Relevance
“…Perovskite films fabricated via traditional solution process are prone to produce defects at the surfaces and GBs, which serve as non‐radiative recombination centers leading to an overall reduction of efficiencies and poor stability of the device [10] . The chemical passivation of those defects can be rationalized into two main strategies: i. mixing additive substances in the precursor solutions [11, 12] or antisolvents [13–16] to control perovskite growth and/or passivate defects in perovskite GBs; ii. surface modification via coating functional molecules on the preformed perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskite films fabricated via traditional solution process are prone to produce defects at the surfaces and GBs, which serve as non‐radiative recombination centers leading to an overall reduction of efficiencies and poor stability of the device [10] . The chemical passivation of those defects can be rationalized into two main strategies: i. mixing additive substances in the precursor solutions [11, 12] or antisolvents [13–16] to control perovskite growth and/or passivate defects in perovskite GBs; ii. surface modification via coating functional molecules on the preformed perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, a solution of conjugated N, N′‐bis‐(7,7,8,8,9,9,10,10,11,11,12,12,12‐tridecafluoro dodecan‐5‐yl)‐perylene‐3,4,9,10‐tetracarboxylic diimide (FPD) in chlorobenzene (CB) is used as the antisolvent (anti‐solution), to implant the FPD inside the film during the nucleation of perovskites. This protocol ensures that the defects (e.g., noncoordinating Pb 2+ ) at GBs be passivated by the carbonyl groups (C=O), and the fluorine atoms can form hydrogen bonds with MA + to immobilize the cations, thus ensuring thermal stability [13–15, 35] . Secondly, a hydrophobic 2D perovskite layer is formed in situ on the 3D perovskite layer by successively depositing 2‐(2‐Fluorophenyl)ethylamine iodide after the antisolvent‐treatment to passivate the defects on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed to overcome the instability issues associated with perovskite materials. There have been attempts to modify three-dimensional (3D) perovskite by using additives [ 6 ], introducing intermediate phases [ 7 ], encapsulating the layers [ 8 ], etc. Several studies have been dedicated to analyzing the effect of mixed cations and halides to enhance PSCs’ stability and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Thechemical passivation of those defects can be rationalized into two main strategies:i . mixing additive substances in the precursor solutions [11,12] or antisolvents [13][14][15][16] to control perovskite growth and/or passivate defects in perovskite GBs;i i. surface modification via coating functional molecules on the preformed perovskite layer. Va rious organic molecules [17][18][19][20] and polymers [21][22][23][24] have been applied to chemically passivate the defects on the perovskite surface in PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] In this context, we introduce ac omprehensive dualpassivation (DP) strategy to realize the passivation of defects both inside the GBs and over the surface.Firstly,asolution of conjugated N, N'-bis- (7,7,8,8,9,9,10,10,11,11,12,12,12-tridecafluoro dodecan-5-yl)-perylene-3,4,9,10-tetracarboxylic diimide (FPD) in chlorobenzene (CB) is used as the antisolvent (anti-solution), to implant the FPD inside the film during the nucleation of perovskites.T his protocol ensures that the defects (e.g.,n oncoordinating Pb 2+ )a tG Bs be passivated by the carbonyl groups (C=O), and the fluorine atoms can form hydrogen bonds with MA + to immobilize the cations,t hus ensuring thermal stability. [13][14][15]35] Secondly,ahydrophobic 2D perovskite layer is formed in situ on the 3D perovskite layer by successively depositing 2-(2-Fluorophenyl)ethylamine iodide after the antisolvent-treatment to passivate the defects on the surface.A sar esult, the novel DP strategy prolongs carrier lifetime through defect passivation and, hence,lifts the V OC from 1.10 Vt o1 .18 V, corresponding to a V OC deficit of 0.39 V. In the complete devices,w ea chieved ac hampion stabilized PCE as high as 23.80 %. It is found that besides the excellent thermal and moisture resistant properties [9,14,18,33,36,37] provided by the DP strategy,t he effective passivation of site-vacancy-type defects (e.g., iodine vacancy) successfully suppressed the generation of O 2 À species.E specially,t his is the first time to observe the decrease of destructive O 2 À species by forming a2 Dp erovskite layer.…”
Section: Introductionmentioning
confidence: 99%